The optimization and modeling of PCP wastewater using response surface methodology by electrocoagulation process - Guvenc, Senem Yazici (DESALINATION PUBL, 2017)
In this study, electrocoagulation process was performed using Al and Fe electrodes for personal care product (PCP) industry wastewater treatment. Response surface methodology approach using Central Composite Design was applied to develop a mathematical model and optimize process parameters (initial pH, current density and electrolysis time) for chemical oxygen demand (COD) and total suspended solids (TSS). The predicted values of models obtained using RSM were in good agreement with experimental data. The optimu m conditions for the COD removal were found to be pH of 8.03, current density of 58 mA/cm(2), electrolysis time of 33 with Al electrodes, whereas the optimum conditions were pH of 5.9, current density of 75 mA/cm(2), electrolysis time of 45 min with Fe electrodes. Under optimum conditions, 97.09% COD removal was obtained using Al electrodes and 98.76% COD removal was obtained using Fe electrodes. The operating costs for the COD removal from PCP wastewater by electrocoagulation process using Al and Fe electrodes at optimized conditions were calculated to be 3.75 and 3.86 sic/m(3), respectively. Additionally, the sludge samples formed in the process was characterized by Fourier transform infrared spectroscopy (FT-IR) analysis. According to FT-IR results, pollutants in PCP wastewater were linked to Al(OH)(3) and Fe(OH)(3) compounds.
Keywords: PCP wastewater; Electrocoagulation; RSM; Cost analysis; Sludge characterization; PERSONAL CARE PRODUCTS; REMOVAL; PHARMACEUTICALS; WASTEWATERS; DESIGN; FENTON; SLUDGE; Engineering; Water Resources